2012
DOI: 10.1001/archpediatrics.2011.1839
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Nutrient Intake Associated With State Laws Regarding Fat, Sugar, and Caloric Content of Competitive Foods

Abstract: To determine whether nutrient intake is healthier among high school students in California, which regulates the nutrition content of competitive foods sold in high schools, than among students in states with no such standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 22 publications
3
28
1
Order By: Relevance
“…In the study analyzed by Taber et al [64], they also found that the California sample had a greater proportion of Hispanic students (76.6%) than other states that were in the sample (14.7%). However, the results were very similar when restricting the analysis to Hispanic students on consumption of caloric content of competitive foods.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study analyzed by Taber et al [64], they also found that the California sample had a greater proportion of Hispanic students (76.6%) than other states that were in the sample (14.7%). However, the results were very similar when restricting the analysis to Hispanic students on consumption of caloric content of competitive foods.…”
Section: Discussionmentioning
confidence: 99%
“…And Hartstein et al [44] noted that two Texas schools in their study showed a reduction in Kcal density from 277 to 216, however, other reductions were modest (1 to 12 Kcal per item sold). California students exposed to more stringent school nutrition policies consumed a lower proportion of their Kcalories at school, indeed, consumed less for every measure examined, compared with students in other states [64]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations